2005
DOI: 10.1097/01.ju.0000169422.46721.d7
|View full text |Cite
|
Sign up to set email alerts
|

Bulbar Urethroplasty Using Buccal Mucosa Grafts Placed on the Ventral, Dorsal or Lateral Surface of the Urethra: Are Results Affected by the Surgical Technique?

Abstract: In our experience the placement of buccal mucosa grafts into the ventral, dorsal or lateral surface of the bulbar urethra showed the same success rates (83% to 85%) and the outcome was not affected by the surgical technique. Moreover, stricture recurrence was uniformly distributed in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(176 citation statements)
references
References 13 publications
5
165
0
6
Order By: Relevance
“…The first was designed to look specifically at a comparison of dorsal versus ventral application of the BM graft . 7 The study included 50 patients, of whom 17 had the graft applied ventrally, 27 dorsally, and 6 laterally within the urethra. They reported a similar success rate of 83-85% in all groups.…”
Section: Dorsal Onlaymentioning
confidence: 99%
See 1 more Smart Citation
“…The first was designed to look specifically at a comparison of dorsal versus ventral application of the BM graft . 7 The study included 50 patients, of whom 17 had the graft applied ventrally, 27 dorsally, and 6 laterally within the urethra. They reported a similar success rate of 83-85% in all groups.…”
Section: Dorsal Onlaymentioning
confidence: 99%
“…7 With this in mind the authors performed a literature review to ascertain whether the updated literature was more indicative of which technique results in the best outcomes for BM urethroplasty, and should therefore for preference be used clinically.…”
mentioning
confidence: 99%
“…Barbagli et al [9] found that all three sites were associated with similar outcomes. On review of literature it was found that both dorsal and ventral BMG augmentation urethroplasties were associated with similar outcomes (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…On review of literature it was found that both dorsal and ventral BMG augmentation urethroplasties were associated with similar outcomes (Table 2). [9][10][11][12] Proponents of dorsal placement of graft argue that there is decreased chance of diverticula formation and better chance of neovascularisation with the graft lying on cavernosal bodies which would not be seen if the graft is placed ventrally. The proponents of ventral placement in bulbar urethra argue that it offers better access to proximal site of stricture, less mobilization of urethra preserving its vascularity in addition to the fact that the bulbocavernous muscle prevents diverticula formation.…”
Section: Discussionmentioning
confidence: 99%
“…In urethral stenosis treatment, it is important to take into account its localization, extension and degree of fibrosis of the corpus spongiosum (6). The endoscopic treatment of stenosis through the incision of the fibrotic tissue, with its posterior reepithelization, can be an option when the stenotic segment is short and has a limited degree of fibrosis (7).…”
Section: Introductionmentioning
confidence: 99%